Kajian penerapan arsitektur organik pada kawasan agrowisata - Gina Liana Wati; Anisa (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Organic architectural study on agro-tourism areas Organic architecture is a concept in architecture that is in harmony with nature and integrated with the site through visualization. There are eight basic concepts that can be used as a reference in designing organic architectural building concepts, namely, building as nature, continuous present, form follows flow, of the people, of the hill, of the material, youthful and unexpected, Living music. modern agro-tourism areas can liven up the atmosphere of modern agro-tourism areas, so as to increase the attractiveness of these modern agro-tourism areas. This study used a deductive method to find out more about the application of organic architecture in the Farm Kuntum region. The analysis was conducted descriptively qualitatively using the theory of eight organic architectural concepts. The conclusion obtained is that the concept of organic architecture can be applied to modern agro-tourism areas, including applying open mass compositions and resembling organisms, presenting natural elements, and making nature part of the design an application of the building is nature concept. The form follows flow is applied to modern agro-tourism areas by designing the longest side of the building to the north and south, designing the building with openings, and designing an open area leading to a beautiful natural environment. Of the people is applied to modern agro-tourism areas by providing sufficient space for visitors to interact with animals and design buildings with open spaces that can accommodate large crowds. © 2020 Anisa, Gina Liana Wati